2019
DOI: 10.1002/ptr.6447
|View full text |Cite
|
Sign up to set email alerts
|

Nardostachys chinensis Batalin: A review of traditional uses, phytochemistry, and pharmacology

Abstract: Nardostachys chinensis Batalin (Valerianaceae) has been widely used in different traditional systems of medicine, including Islamic, Ayurvedic, Chinese, and Korean folk medicine. It has been used in traditional medicine as a tranquilizer, hepatotonic, cardiotonic, diuretic, and analgesic. Preliminary in vitro and in vivo studies have provided valuable scientific evidence for its traditional uses. This review aims to summarize reported traditional uses, phytochemistry, and pharmacological potential of N. chinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…( Valeriana rubra L., commonly known as red valerian, red spur valerian, and spur valerian) are used in Italy as depurative [ 17 ]. N. chinensis has been used in some traditional medicines, including Chinese, Korean, and Ayurvedic medicine to treat epilepsy, hysteria, hyperglycemia, dyslipidemia, headache, stress indigestion, heart palpitations, mental weakness, cholera, and leprosy [ 18 ]. The leaves of Fedia cornucopieae (L.) Gaertn.…”
Section: Habitat Distribution and Traditional Uses Of Valerianaceae Sub-familymentioning
confidence: 99%
“…( Valeriana rubra L., commonly known as red valerian, red spur valerian, and spur valerian) are used in Italy as depurative [ 17 ]. N. chinensis has been used in some traditional medicines, including Chinese, Korean, and Ayurvedic medicine to treat epilepsy, hysteria, hyperglycemia, dyslipidemia, headache, stress indigestion, heart palpitations, mental weakness, cholera, and leprosy [ 18 ]. The leaves of Fedia cornucopieae (L.) Gaertn.…”
Section: Habitat Distribution and Traditional Uses Of Valerianaceae Sub-familymentioning
confidence: 99%
“…Nardostachys jatamansi DC., which has been extensively used for centuries in Himalayan countries to treat neurological and cardiovascular diseases [1,2], presents bioactive constituents such as nardosinone, nardosinonediol, isonardosinone, desoxo-narchinol A, and aristolone, which play crucial roles in the plant's therapeutic properties [2]. Among these constituents, nardosinone is integral for the authentication and quality evaluation of N. jatamansi [3][4][5], and it is stipulated to constitute at least 0.1% of the dried processed roots and rhizomes of the plant, according to the Chinese Pharmacopoeia [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nardostachyos Radix et Rhizoma (NRR), the root and rhizome of Nardostachys jatamansi DC., has the traditional pharmacological action of regulating qi, relieving pain, and relieving stagnation-syndrome, and is often used as the raw material for spices, food and cosmetics [ 7 ], and contains multiple chemical constituents, such as terpenes, flavonoids, coumarins, lignans, and volatile oils [ 8 ], of which sesquiterpenoids (e.g., nardosinone) are the main active components [ 9 ]. Pharmacological studies have shown that NRR has pharmacological effects of improving headaches, palpitations, and syncope [ 9 ], and it also has antioxidant, neuroprotective, antiepileptic, cardioprotective, anti-neuroinflammation, and other pharmacological activities [ 10 , 11 , 12 ]. Furthermore, NRR is mainly used in the form of compound prescription in clinical, e.g., Wenxin Granules can be used to treat premature ventricular contractions in patients with chronic heart failure [ 1 ].…”
Section: Introductionmentioning
confidence: 99%